Accurate assessment of the output energy from the doubly fed induction generators. (15th December 2015) - El-Kharashi, Eyhab; Farid, Azmy Wadie
Abstract: Wind energy shows considerable promise for the future. Doubly fed induction generators (DFIGs) are attracting much attention in wind energy systems due to their unique advantages, including a reduced size power converter, as well as versatility in the independent control of active and reactive power. It is important to determine the precise output energy from the DFIG, particularly when the output voltage is unbalanced, in order to be able to undertake an accurate assessment of the entire output energy from the wind farm. This paper presents a new model for the doubly fed induction generator operating under unbalanced conditions. This model is deduced using the space vector and the angle of unbalanced current for the stator and the rotor currents. This model is used for the precise assessment of the output energy from the doubly fed induction generator, whether it generates either a balanced or unbalanced supply of voltage. Also the paper introduces a power circle diagram which translates the use of the proposed mathematical model by a simple way to stand one of the degrees of the unbalance during the unbalanced operation. Highlights: The paper presents a new model for the doubly fed induction generator operating under unbalanced conditions. It is deduced using the space vector and the angle of unbalanced current. This model is used for the precise assessment of the output energy from the doubly fed induction generator. Also the paper introduces a power circle diagram to simplify the use of the model.